Letter from Maurice Wilkins to Aaron Klug, April 26, 1963 - Wilkins, Maurice (1963)
Letter from Aaron Klug (1926-2018) to Maurice Wilkins (1916-2004), written April 26, 1963. Klug shares his thoughts on a paper written by Bruce Fraser (1924-2019) and "MacRae".
Keywords: Wilkins, Maurice, 1916-2004; Fraser, Robert Donald Bruce, 1924-; Klug, A. (Aaron), Sir, 1926-2018